Microhabitat Assessment of Mangrove Pit Viper Cryptelytrops purpureomaculatus in Restricted Mangrove Area, Dumai, Riau Province, Sumatera - Nia Kurniawan; Bagus Priambodo; Fitra Arya Dwi Nugraha; Andri Maulidi; Agung Sih Kurnianto (Journal of Tropical Life Science, 2017)
Bandar Bakau is a mangrove conservation area with approximately 20 ha that preserves many kinds of fauna, including Mangrove Pit Viper Cryptelytrops purpureomaculatus. However, this species and its habitat are still poorly studied in Indonesia, particularly Sumatera island, despite it has a wide distribution in Southeast Asian countries. The main purpose of this study is to evaluate the microhabitat of Mangrove Pit Viper C. purpureomaculatus that found at a restricted mangrove area in Dumai, Riau Province. Visual Encounter Survey (VES) and deep interview methods were used in this study. The survey found six individuals of C. purpureomaculatus that mostly basking on the Avicennia marina and artificial building. Although Bandar Bakau is a tourism object, but no snakebite cases were found.